Optical magnetic response without metamaterials - Li, Jinxiang (2022)
One of the main achievements of metamaterials research has been the development of structured matter exhibiting optical magnetism: first, in an array of microwave split-ring resonators and, soon after, in plasmonic and dielectric metamaterials at THz to visible frequencies. We show here that metamaterial structuring is not necessary to achieve optical magnetic response. Indeed, such a response is an essential characteristic of homogeneous dielectric thin films—Fabry-Pérot resonances, for example, depend on interference among electromagnetic multipoles including the magnetic dipole.